Design of Laboratory Scale Fluid Level Measurement Device Based on Arduino - Apsari, Nur Fitri; Megantoro, Prisma; Sattar, Mian Usman; Maseleno, Andino; Tanane, Omar (Journal of Robotics and Control (JRC), 2020)
Measuring the height of a liquid using analog is very difficult, and its accuracy is very low. It is more accurate to measure liquid level using digital technology. Measurements of the correct fuel level are needed to measure fuel purchases at fuel stations or fuel retailers. The study aimed to design laboratory-level fuel level measurements based on the Arduino Uno microcontroller. The method used was a direct comparison between the measuring instrument and a ruler as a measuring standard. This device used a gas gauging sensor on the vehicle and an Arduino Uno microcontroller to process data and display data on the LCD and LabView. The results of the fluid level measurement could be used to determine the height of fuel surface. The error rate of the measuring instrument was Â± 3% in a calm and bumpy state. The results showed that the device is suitable for use in measurement.